ACCURACY OF BODY WEIGHT ESTIMATION IN BALI CATTLE (BOS JAVANICUS) USING LAMBOURNE, SCHOORL, DJAGRA, WINTER, AND MULTIPLE LINEAR REGRESSION EQUATIONS - Nurliani Erni; Muhammad Rido; Teguh Rafian; suhardi; Ari Wibowo (Universitas Muhammadiyah Malang, 2026)
This study aimed to evaluate the accuracy level of Bali cattle (Bos javanicus) body weight estimation using the Lambourne, Schrool, Djagra, and Winter formulas, and to develop a multiple linear regression model as an alternative method for estimating Bali cattle body weight. The sample consisted of 23 female Bali cattle aged 1–1.5 years based on recording data, selected using a purposive sampling method. The method involved collecting data on chest girth, body length, and actual body weight measured using a weighing scale. The data were analyzed descriptively to obtain the mean, standard deviation, coefficient of variation, estimated body weight calculation results, and percentage bias of the Lambourne, Schrool, Djagra, and Winter formulas, as well as multiple linear regression analysis using IBM SPSS Statistics 22. The average body weight measured using the scale was 152.48 kg, while the estimated body weights were 157.26 kg using the Lambourne formula with a bias of 3.14%, 233.89 kg using the Schrool formula with a bias of 53.39%, 154.34 kg using the Djagra formula with a bias of 1.18%, and 157.62 kg using the Winter formula with a bias of 3.37%. It was concluded that the Djagra formula had the highest level of accuracy, and the regression equation BW = -257.29 + 2.18(CG) + 1.25(BL) with a coefficient of determination of 0.96 can be used as a formula for estimating Bali cattle body weight.